Rus’, Hungary and the Holy Roman Empire in the International Relations of The Second Third of the 13th Century: Actual Problems of Historiography - Чугуй, Тарас (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2019)
The paper analyzes pressing questions of Rus’-Hungarian-Austrian relations at the time of the kings Danylo Romanovich and Bela IV. The historiographical coverage of the discussion aspects of the interstate relations of Rus’, Hungary, the Holy Roman Empire, Poland and the Golden Horde is considered. The peculiarities of the completion of the Romanovich struggle for the parental heritage, the significance of the Hungarian factor in the domestic and foreign policy of Danylo Romanovich are clarified. The conclusion about the importance of the Rus’-Hungarian-Austrian relations in the history of the Galician and Volyn lands in 1235–1264 was drown.